Analysis of The Effect of Adding CMC Additive from Sunflower Seed Hull on The Rheology of Drilling Mud and Filtration Loss - Andreas, Andreas; Malrin, Engeline; Amiruddin , Amiruddin (Green Publisher Indonesia, 2026)
Drilling mud is a drilling fluid used to transport cuttings to the surface and assist in identifying subsurface formation layers; therefore, proper drilling mud design is essential for the success of drilling operations. One common problem in drilling activities is insufficient mud viscosity, which necessitates the addition of additives. Carboxymethyl cellulose (CMC) is commonly used to improve mud viscosity; however, its synthetic nature may pose environmental concerns. This research investigates the use of organic waste in the form of sunflower seed shells as an environmentally friendly alternative additive. Sunflower seed shells contain natural components, including cellulose, hemicellulose, and lignin, which may enhance mud viscosity. The objective of this study is to evaluate the effect of sunflower seed shell powder on the rheological properties of drilling mud and to compare its performance with that of CMC. The research was conducted through laboratory experiments at the STT Migas Balikpapan Laboratory. Rheological tests included viscosity over time, plastic viscosity, yield point, gel strength, mud cake thickness, and filtration loss. Mud samples were prepared with the addition of CMC and sunflower seed shell powder at concentrations of 1 g, 3 g, and 5 g. The results show that increasing the concentration of sunflower seed shell powder improves the rheological properties of drilling mud and reduces filtration loss. Although its performance is lower than that of CMC, sunflower seed shell powder demonstrates potential as an environmentally friendly alternative additive for drilling mud.